The circus ship - Van Dusen, Chris (Somerville, Mass. : Candlewick Press, 2009)
When a circus ship runs aground off the coast of Maine, the poor animals are left on their own to swim the chilly waters. Staggering onto a nearby island, they soon win over the wary townspeople with their kind, courageous ways. So well do the critters blend in that when the greedy circus owner returns to claim them, villagers of all species conspire to outsmart the bloated blowhard.
Chickadee Award, 2010-2011.
Keywords: Circus animals -- Juvenile fiction; Circus -- Juvenile fiction; Islands -- Juvenile fiction; Stories in rhyme; Humorous stories; Maine -- Juvenile fiction